A novel UPLC–MS/MS method for simultaneous quantification of trigonelline, 4‐hydroxyisoleucine, and diosgenin from Trigonella foenum‐graecum extract: Application to pharmacokinetic study in healthy and type 2 diabetic rats. (16th November 2021) - Wadhwa, Geetika; Krishna, Kowthavarapu Venkata; Taliyan, Rajeev; Tandon, Neeraj; Yadav, Satyapal Singh; Banerjee, Dipankar; Narwaria, Avinash; Katiyar, Chandrakant; Dubey, Sunil Kumar
Abstract: Trigonelline (TR), 4‐hydroxyisoleucine (4‐HI), and diosgenin (DG) are the main bioactives of the purified standardized extract of the popular plant Trigonella foenum‐graecum L. (TFG), and it has been proven effective for the treatment of various diseases. However, to the best of our knowledge, no study has investigated the pharmacokinetic parameters of purified standardized T. foenum‐graecum extract in normal and diabetic Wistar rats. The present study has developed and validated a rapid, reliable, and sensitive simultaneous ultra‐performance liquid chromatography MS method to estimate these bioactives. The chromatographic separation was achieved using methanol, acetonitrile, and 0.1% formic acid with the ideal gradient flow system on a BEH Shield RP 18 column. A positive electrospray ionization mode was selected to estimate m/z values of TR (138.14 > 94.63), 4‐HI (148.19 > 74.08), and DG (415.54 > 271.33). The method was robust and reproducible over the linearity range of 60–5000, 6–5000, and 15–5000 ng/mL for TR, 4‐HI, and DG, respectively. Using this novel validated method, we investigated the pharmacokinetic parameters of bioactives using Phoenix WinNonlin version 8.0 (Certera) in normal and diabetic rats. The assay was successfully applied for the estimation of pharmacokinetic parameters using noncompartmental analysis. This investigation shows that the absorption rate increased, whereas distribution and elimination processes slowed down in diabetic rats compared with normal rats. Abstract :